A feature-based algorithm for image mosaics with moving objects - Zhang Dakun; Li Zhaoxin; Jiang Guiyuan (2010 IEEE International Conference on Intelligent Computing and Intelligent Systems, 2010)
A feature-based algorithm for image mosaics with moving objects is proposed. Firstly, the algorithm eliminates feature points which are selected on moving objects during similarity transform, then outliers are eliminated using RANSAC algorithm. In the image blend phase, difference image between two images is created using homogeneous transformation matrix. Then region growth algorithm is used to segment the moving object region. Finally, a piecewise mapping algorithm for generating panoramic images is utilized. Experimental results show the effectiveness of the algorithm.